The Relationship Between Knowledge Of Women Of Childbearing Age And Paps Smear In The Work Area Of The West Mandere Non-Inpatient Health Center In 2024 - Zuidah, Zuidah; Sumiatik, Sumiatik (Jurnal EduHealth, 2024)
Early detection of cervical cancer can be done by performing a pap smear. Pap smear is a gynecologic screening method to find premalignant or premalignant processes and malignancy or malignancy in the cervix. Some of the factors that can influence a person's behavior towards a pap smear examination are knowledge and action. This study aims to find out the overview of the relationship between the knowledge of women of childbearing age and the action of Paps Smear in the Working Area of the West Mandere Non-Inpatient Health Center in 2024. The type of research used is descriptive research. This research was carried out in the Working Area of the West Mandere Non-Inpatient Health Center with a sample of 30 people, Data collection was carried out using a questionnaire. Basil the research showed that the majority of respondents had less knowledge as many as 12 people (40.0%). The actions of respondents were insufficient in conducting papssmear examinations for 18 people (60.0%). Based on statistical tests using the Chi Square method (α = 0.05), the result of p value = 0.002 was obtained. The value < 0.05 so that Ha is accepted, which means there is a significant relationship. Based on the results of the study, it can be concluded that WUS has low knowledge and lack of understanding about the importance of pap smear examination and WUS has not received and given a good response in terms of pap smear examination as one of the steps for early detection of cervical cancer. It is still necessary to increase knowledge and attitudes.